School-Related Factors Influencing the Self-Concepts of Children with Learning Problems. - Smith, Monte D.; Dokecki, Paul R.; Davis, Earl E. (Peabody Journal of Education (0161956X))
Focuses on the school-related factors that influence the self-concepts of children with learning disabilities. Characteristics of the children; Conceptualization and measurement of self-concept in children; Results of different investigations on the self-concepts of children.